An acid and alkali-resistant triboelectric nanogenerator. Issue 45 (18th November 2020) - Wu, Jun-Peng; Liang, Wen; Song, Wei-Zhi; Zhou, Li-Na; Wang, Xiao-Xiong; Ramakrishna, Seeram; Long, Yun-Ze
Abstract : An acid- and alkali-resistant TENG based on a superhydrophobic sintered PVA–PTFE composite membrane. Abstract : With the development of technology, environmental problems have become more and more acute and the use of electronic devices in harsh environments has gradually attracted attention. For example, the friction layer of triboelectric nanogenerators (TENGs) may be contaminated and corroded in harsh environments (such as acidic, alkaline or oily environments), resulting in damage or destruction of the TENGs. In this study, we use electrospinning followed by a sintering process to prepare a super-hydrophobic sintered polyvinyl alcohol–polytetrafluoroethylene (S-PVA–PTFE) composite membrane and general industrial oil-absorbing paper to construct a TENG. The maximum power density of the TENG is 261 mW m −2, it can light up 100 blue LEDs, and can power a variety of small electronic devices. Moreover, after 72 h of soaking the friction layer in a strong acid solution followed by a strong alkali solution, the performance of the TENG has no obvious change. The TENG can work stably in an oily working environment. The TENG provides a novel approach for self-powered sensors that work in harsh environments.